The Informative Role of the Value Line Investment Survey: Evidence from Stock Highlights - Peterson, David R. (Journal of Financial and Quantitative Analysis, 1995)
David R. Peterson, The Informative Role of the Value Line Investment Survey: Evidence from Stock Highlights, The Journal of Financial and Quantitative Analysis, Vol. 30, No. 4 (Dec., 1995), pp. 607-618